2019
DOI: 10.3390/v11090795
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Pregnant Female Sheep with Zika Virus During Early Gestation

Abstract: Zika virus (ZIKV) is a vertically and sexually transmissible virus resulting in severe congenital malformation. The goal of this study was to develop an ovine model of ZIKV infection. Between 28–35 days gestation (DG), four pregnant animals were infected with two doses of 6 × 106 PFU of ZIKV; four control animals received PBS. Animals were evaluated for 45 days (D) post-infection (PI) and necropsies were performed. Viral RNA was detected in infected ewe peripheral blood mononuclear cells (PBMC) during the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 75 publications
7
17
1
Order By: Relevance
“…Furthermore, previous research indicates that the viral kinetics of ZIKV in fetal sheep cells has been shown to be similar to that in immortalized Aedes albopictus cells [26]. We have also demonstrated that immortalized adult sheep kidney cells and immortalized fetal sheep testicular cells are susceptible to ZIKV infection and can sustain viral replication for many days [25].ZIKV is also unique in that sexual transmission occurs with infection of the male reproductive tract with possible establishment of prolonged, asymptomatic infection in men [27][28][29][30]. This carrier status in males may make men more likely to sexually transmit ZIKV to females than vice versa [1].…”
supporting
confidence: 70%
See 4 more Smart Citations
“…Furthermore, previous research indicates that the viral kinetics of ZIKV in fetal sheep cells has been shown to be similar to that in immortalized Aedes albopictus cells [26]. We have also demonstrated that immortalized adult sheep kidney cells and immortalized fetal sheep testicular cells are susceptible to ZIKV infection and can sustain viral replication for many days [25].ZIKV is also unique in that sexual transmission occurs with infection of the male reproductive tract with possible establishment of prolonged, asymptomatic infection in men [27][28][29][30]. This carrier status in males may make men more likely to sexually transmit ZIKV to females than vice versa [1].…”
supporting
confidence: 70%
“…Furthermore, previous research indicates that the viral kinetics of ZIKV in fetal sheep cells has been shown to be similar to that in immortalized Aedes albopictus cells [26]. We have also demonstrated that immortalized adult sheep kidney cells and immortalized fetal sheep testicular cells are susceptible to ZIKV infection and can sustain viral replication for many days [25].…”
supporting
confidence: 69%
See 3 more Smart Citations